Novel surgical machining via an impact cutting method based on fracture analysis with a discontinuum bone model. Issue 1 (2017) - Sugita, Naohiko; Shu, Liming; Shimada, Takehiro; Oshima, Masaya; Kizaki, Toru; Mitsuishi, Mamoru
Abstract: Cutting (including sawing and drilling) is a common procedure in orthopedics. Although it is widely used, cutting is associated with surgical problems, such as bone breakthrough and necrosis. In this study, the phenomenon of large fractures was analyzed with a discontinuum model of a bone by initially predicting crack propagation. A cutting method utilizing impacts by vibration was then proposed, and experiments were performed. The results indicated that the principal cutting force decreased by more than 80% in each cutting direction. The findings suggest that the method can realize low load, high efficiency, and high accuracy of bone machining.